Seismic and non-seismic soft-sediment deformation structures in the Proterozoic Bhander Limestone, central India - Sarkar, Subir; Choudhuri, Adrita; Banerjee, Santanu; van Loon, A.J. (Tom); Bose, Pradip K. (Bogucki Wydawnictwo Naukowe, 2014)
Numerous soft-sediment deformation structures occur within the Proterozoic Bhander Limestone of an intracratonic sag basin in a 750 m long section along the Thomas River, near Maihar, central India. Part of these deformation structu -res have most probably a non-seismic origin, but other structures are interpreted as resulting from earthquake-induced shocks. These seismic structures are concentrated in a 60 cm thick interval, which is interpreted as three stacked seismi -tes. These three seismites are traceable over the entire length of the section. They divide the sedimentary succession in a lower part (including the seismites) deposited in a hypersaline lagoon, and an upper open-marine (shelf) part. Most of the soft-sediment deformations outside the seismite interval occur in a lagoonal intraclastic and muddy facies asso -ciation. The SSDS within the seismite interval show a lateral continuity. They record simultaneous fluidisation and liquefaction. The bases of each of the three composing seismite bands are defined by small-scale shear folds, probably recording an earthquake and aftershocks. The presence of the three seismite bands at the boundary between the lagoonal and the overlying open-marine oolitic facies association suggests that the seismic event also triggered basin subsidence.
Keywords: Seismites; Soft-sediment deformation structures; Basin subsidence; Bhander Limestone; Proterozoic; India